Dispelling the Ambivalence of Salt Farmer Welfare Policy: Study of Grassroots Ethnography in Local Wisdom Innovation in Mangunlegi Village - Aulia, Hana; Asyraf, Muhammad Affan; Febriani, Untari; Iffah, Rona; Kastiureni, Seren (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2022)
Economic problems and the complexity of salt production have riddled government policies to alleviate salt farmers’ poverty. This raises the question of how to optimise policies that can impact the welfare of salt farmers. Based on this problematization, this paper attempts to explore the ambivalence of government intervention in the PUGAR (People’s Salt Business Empowerment) policy to alleviate poverty for salt farmers in Mangunlegi Village, Batangan District, Pati. Using an ethnographic approach, the search for policy studies that link the community and the government has illustrated the complexity of the economic growth of salt farmers in Mangunlegi. This complexity is shown by the declining income growth of salt farmers amid the presence of a survival strategy in articulating the meaning of local wisdom and the social environment when people adapt to government policies. The results of this study rest on the possibility of achieving the welfare of Mangunlegi salt farmers through their adaptability to government policies, which lead to grassroots social innovation. For this reason, this study pays attention to the implications of the research results, which reveal that the welfare of salt farmers can be realised if the policies issued by the government do not cause ambivalence. However, if salt farmers are given the freedom to formulate grassroots-based policies, social innovation can be realised. This is one of the solutions to poverty alleviation for salt farmers in Mangunlegi.